Gross Anatomy of the Reproductive Tract and Oestrous of the Malayan Tapir (Tapirus indicus). - Koo, Li Lia (2010)
This study was carried out in view of the declining wild population of Malaysian Tapir (Tapirus indicus) which is mainly due to human encroachment into their natural habitat. This has led to the displacement of this species of which occurrences have been observed in various states in Peninsular Malaysia. Some of the displaced tapirs that were rescued survived, although this was not always the case. In the captive situation in Peninsular Malaysia, most tapirs are individually housed except for the occasional few who are compatible and can live in pairs. At the moment, there are no planned breeding programmes in any of the captive facilities housing this species. Therefore, this study was carried out to study the reproductive status of the female Malaysia tapir. The objectives of this study were to establish the oestrous cycle, evaluate the gross female reproductive anatomy and to create reference data which can be used to evaluate the reproductive status of female Malaysian tapirs in other captive facilities in the country. Plasma progesterone concentration analysis and ultrasound examination of the reproductive tracts were carried out on three female adult tapirs in Zoo Melaka, Melaka; while gross examination of the female reproductive tracts was done on necropsied samples available during the period of study. Blood was collected twice weekly and the plasma was frozen and stored until analysed. Ultrasound examination was also performed twice weekly. The female tapirs were conditioned to both these procedures several month before the study began. Plasma progesterone concentration was analyzed using radioimmunoassay to establish the oestrous cycle of the Malayan tapir for a year. Two oestrous cycle patterns were observed in three females understudy. One tapir had a cycle of 35 ± 1.9 days with a range of 22 to 47 days. The other female had oestrous cycle length OF 65 ± 4.3 days with a range of 33 to 82 days while the third female had a cycle length of 65 ± 9.5 days with a range of 43 to 88 days. Tapirs have bicornuate uterus and relatively small and elongated ovaries. While the ovaries were difficult to scan using ultrasound, the firm muscular cervix was easily detected and had a “spokes-wheel” appearance. Results obtained from this study provide a useful reference for the Department of Wildlife and National Parks of Peninsular Malaysia and local zoos in the country to evaluate the reproductive status of tapirs in captivity. Once the reproductive status of the tapirs in captivity is established, proper breeding, programmes can be planned to increase the species population in effort of conserving this species.